MENGUKUR KETERLIBATAN PELANGGAN EFEKTIF PADA INDUSTRI MAKANAN CEPAT SAJI: PENGARUH PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Yosephine, Thalia; Purnama Sari, Desak Made Febri; Pradhana, I Putu Dharmawan; Laksmi P, Kadek Wulandari (JURNAL ILMIAH EDUNOMIKA, 2025)
This study investigates the influence of Perceived Enjoyment and Perceived Originality on Purchase Decision and Affective Customer Engagement among fast-food consumers in Bali, with Positive Word of Mouth as a mediator. Findings show both Perceived Enjoyment and Perceived Originality positively impact PWOM, which subsequently influences Purchase Decision and Affective Customer Engagement. Direct effects were also noted. PWOM strongly mediates the relationship between Perceived Enjoyment and Purchase Decision (VAF 61.9%), but its mediation between Perceived Originality and Affective Customer Engagement is very weak (VAF 13.5%), suggesting other underlying mechanisms. Fast-food producers in Bali should enhance originality and enjoyable experiences to foster PWOM and emotional engagement. The model, though predictively relevant (Q2 = 0.956), explains only a portion of the variance (AVE 61.4%, PWOM 65.5%, PD 66.1%), indicating external factors. Future research should explore these variables and consider qualitative approaches to fully understand complex consumer perceptions. Keywords : perceived enjoyment, consumer experience, fast food, literature review, consumer behavior